1999
DOI: 10.1074/jbc.274.6.3764
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cα Regulates Human Monocyte O·̄2Production and Low Density Lipoprotein Lipid Oxidation

Abstract: Our previous studies have shown that human native low density lipoprotein (LDL) can be oxidized by activated human monocytes. In this process, both activation of protein kinase C (PKC) and induction of superoxide anion (O 2 . ) production are required. PKC is a family of . by superoxide dismutase prevented LDL oxidation (2, 3). General antioxidants such as butylated hydroxytoluene, vitamin E, and ascorbate also inhibited monocyte-mediated oxidation of LDL (2, 4, 5). We also found that increases in intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 45 publications
(55 reference statements)
3
59
1
Order By: Relevance
“…These antisense ODNs were previously characterized and were shown to be selective for their targets in opsonized zymosan-activated human monocytes and not to affect the expression of other isoforms (28). We also characterized these antisense ODN in our system by looking at protein expression by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These antisense ODNs were previously characterized and were shown to be selective for their targets in opsonized zymosan-activated human monocytes and not to affect the expression of other isoforms (28). We also characterized these antisense ODN in our system by looking at protein expression by Western blotting (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment of Cells with ODN-The antisense ODN used in our studies were derived from our prior published work, which reported their efficacy (28,29). The sequence for cPKC-antisense ODN was 5Ј-CCC CAG ATG AAG TCG GTG CA-3Ј, and its control-sense ODN sequence was 5Ј-GGG GTC TAC TTC AGC CAC GT-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…5,11,41 Cellular oxidative modification of cholesterol is thought to involve endothelial-and macrophagederived reactive oxygen species. 36,42,43 Hypertension, which increases arterial wall thickness and oxygen diffusion, produces medial hypoxia and steep oxygen tension gradients within the wall. 44 Recently, compelling evidence was presented that hypoxic areas do indeed exist, particularly in the thickened arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…For human monocytes and RAW264.7 macrophages, it has been shown that the primary event, that is, phosphorylation of p47 phox , is facilitated by protein kinase Ca (PKCa). 7,8 Recently, we demonstrated that downregulation of PKCa or expression of a kinase-dead mutant attenuates the PMA-induced oxidative burst. 9 However, the impact of AC on the oxidative burst remains unknown.…”
Section: Introductionmentioning
confidence: 99%